IMPLEMENTASI AKUNTANSI LINGKUNGAN SEBAGAI INOVASI MATA KULIAH PROGRAM STUDI AKUNTANSI - -, Ratnawati - (Magister Manajemen Universitas Wisnuwardhana, 2016)
Abstract. The development of accounting not only provide information about the activities of the company to a third party (stockholders and bondholders) that have a direct contribution to the company, but demanded summarizes information about the company's relationship with its environment. Environmental accounting applied by various companies to produce a quantitative assessment of the costs and impacts of environmental protection (environmental protection). The achievements in the implementation of environmental accounting in the company needs to be balanced with the implementation of environmental accounting curriculum implemented by universities in the accounting program. In an effort to improve the competence of graduates of Accounting and respond to the trend of global corporate reporting demands, courses in Accounting in Indonesia needs to immediately respond and internalize the environmental accounting in curriculum design and course Accounting. The reason the importance of environmental accounting (green accounting) applied in the course curriculum of accounting due to some situations within the company (the corporate) that require attention and the role of the accountant to provide solutions in the form of reports green accounting report on the costs incurred by the company for the environment , By studying environmental accounting in College students majoring in accounting understands and is able to increase the amount of relevant information that is made for those who need or use. The success of environmental accounting does not only depend on the correctness of classifying all costs made the company, but the ability and accuracy of accounting data of companies in suppressing the environmental impact of the company's activities. Keywords: environmental accounting, accounting course curriculum